Utilizing and Creating Added Value from Commercial Banana: Case Study in Phra Nakhon Si Ayutthaya Province, Thailand - Pakeechai, Kanokporn; Chamuthai, Likit; Samleetes, Kanchanawadee; Klomklaw, Kanokkarn; Mankong, Choklap; Malaipia, Siripron; Srean, Pao; Jaitrong, Somkit; Charoenphun, Narin (Journal of Food Health and Bioenvironmental Science, 2023)
Bananas are an interesting cash crop. The popular banana cultivars that tend to grow commercially in Thailand are Gros Michel banana, Lady Finger banana, Pisang Awak banana (Cultivated banana), and Lebmuernang banana. Banana fruit is a food source rich in nutrients and many important substances. In addition, different parts of the banana can be used and processed to create economic value. Therefore, the knowledge gained from gathering information on banana processing and the feasibility case study of the production of processed products from commercial bananas can be used as a guideline to support and extend the utilization of bananas in various aspects in order to take advantage of local resources as a method to uplift the basic economy to achieve stability, sustainability, increase careers, and income of banana growers and local enterprise.